Developing an Undergraduate Applied Learning Experience - Nelson-Hurwitz, Denise C.; Tagorda, Michelle (Frontiers in Public Health, 2015)
To foster student development, critical thinking, and application skills among public health students at the University of Hawai‘i at Mānoa, a 3-course capstone series was developed as a key component of the public health Bachelor of Arts degree program. Over the course of 1.5 academic years students are actively involved in developing an interdisciplinary project proposal, then executing and presenting an independent, supervised, applied learning project. In the first course, students are introduced to a diverse range of public health projects and methods while working to develop their own project proposal- the foundation for the Applied Learning Experience. The project execution course is designed to allow students to execute their proposed applied learning projects. This experience focuses on the application and integration of public health knowledge, skills, and practice acquired during the bachelor’s degree course of study. Finally, students will be involved in reflecting on, finalizing, and sharing their completed projects in an undergraduate capstone seminar. Through implementation of this series, the program hopes to provide students with the opportunity to actively apply academic skills to real-world application.